A forgotten frontier: spinal cord stimulation for iatrogenic and traumatic peripheral neuropathic pain - Kollenburg, Linda; Arnts, Hisse; Arnts, Inge; van Dongen, Robert; Moser, Heinrich; van Haren, Frank; van Ooijen, Mark; Yong, Robert Jason; Robinson, Christopher L.; Kurt, Erkan (Frontiers in Pain Research, 2025)
IntroductionPeripheral neuropathy (PN) may cause severe, treatment-resistant pain, especially in traumatic and/or iatrogenic cases. In those with insufficient responses to conventional strategies, spinal cord stimulation (SCS) may be a useful treatment option. However, limited research has been performed on SCS for this indication. This study aims to assess the efficacy, satisfaction and safety of SCS in patients with PN caused by traumatic and/or iatrogenic factors.MethodsPatients with traumatic and/or iatrogenic PN, implanted with SCS between 2005 and 2021 at Radboudumc are included in this study. Perioperative data on efficacy, satisfaction, and safety were retrospectively collected from the electronic patient records (EPIC) and analyzed using descriptive statistics. The efficacy is assessed with the numeric rating score (NRS). Responders are defined as those having ≥50% reduction in NRS.ResultsFifteen patients (M = 8, 48 ± 12 years) are included. At last follow-up (2–18 years), 63% (10/15) of patients are defined responders with an average decrease in NRS of 63% (8.1 ± 0.8 to 3.0 ± 2.0) (p < 0.01). All patients are satisfied with their implant. A complication was present in one patient, reporting a superficial infection (6%, 1/15) following implantation.DiscussionUnlike peripheral nerve stimulation (PNS) and dorsal root ganglion (DRG) stimulation, which are more frequently considered for patients with PN caused by traumatic and/or iatrogenic factors, SCS enables central nervous system stimulation via the spinal cord, thus targeting pain regions associated with multiple lower limb nerve roots. As PN, caused by trauma and/or iatrogenic factors may affect multiple nerves simultaneously, it is suggested that SCS offers improved clinical benefit for these patients.ConclusionThe current study demonstrates that SCS is a promising treatment modality for patients with traumatic and/or iatrogenic PN. Prospective trials comparing SCS to treatments like PNS and DRG stimulation are essential to substantiate its efficacy, expand its indications, and inform future clinical guidelines for patients with intractable traumatic or iatrogenic peripheral neuropathy.